Alexithymia is associated with reduced vitamin D levels, but not polymorphisms of the vitamin D binding-protein gene. (August 2021) - Terock, Jan; Hannemann, Anke; Weihs, Antoine; Janowitz, Deborah; Grabe, Hans J.
Abstract : Objective: Alexithymia is a personality trait characterized by difficulties in identifying and describing emotions, which is associated with various psychiatric disorders, including depression and posttraumatic stress disorder (PTSD). Its pathogenesis is incompletely understood but previous studies suggested that genetic as well as metabolic factors, are involved. However, no results on the role of vitamin D and the polymorphisms rs4588 and rs7041 of the vitamin D binding protein (VDBP) have been published so far. Methods: Serum levels of total 25(OH)D were measured in two general-population samples (total n = 5733) of the Study of Health in Pomerania (SHIP). The Toronto Alexithymia Scale-20 (TAS-20) was applied to measure alexithymia. Study participants were genotyped for rs4588 and rs7041. Linear and logistic regression analyses adjusted for sex, age, waist circumference, physical activity, season and study and, when applicable, for the batch of genotyping and the first three genetic principal components, were performed. In sensitivity analyses, the models were additionally adjusted for depressive symptoms. Results: 25(OH)D levels were negatively associated with TAS-20 scores (β = −0.002; P < 0.001) and alexithymia according to the common cutoff of TAS-20>60 (β = −0.103; P < 0.001). These results remained stable after adjusting for depressive symptoms. The tested genetic polymorphisms were not significantly associated with alexithymia. Conclusions: Our results suggest that low vitamin D levels may be involved in the pathophysiology of alexithymia. Given that no associations between alexithymia and rs4588 as well as rs7041 were observed, indicates that behavioral or nutritional features of alexithymic subjects could also explain this association.